Identification of d-Galactan-III As Part of the Lipopolysaccharide of Klebsiella pneumoniae Serotype O1 - Stojkovic, Katarina; Szijártó, Valéria; Kaszowska, Marta; Niedziela, Tomasz; Hartl, Katharina; Nagy, Gábor; Lukasiewicz, Jolanta (Frontiers in Microbiology, 2017)
Klebsiella pneumoniae is a Gram-negative, ubiquitous bacterium capable of causing severe nosocomial infections in individuals with impaired immune system. Emerging multi-drug resistant strains of this species and particularly carbapenem-resistant strains pose an urgent threat to public health. The lipopolysaccharide (LPS) O-antigen is the main surface antigen. It contributes to the virulence of this species and determines the O-serotype of K. pneumoniae isolates. Among nine main O-serotypes of Klebsiella, O1- and O2-type pathogens are causative agents of over 50% of all infections. Serotype O1, the most common O-serotype, expresses complex LPS consisting of D-galactan-I (a polymer built of →3)-β-D-Galf-(1→3)-α-D-Galp-(1→ repeating units) capped by D-galactan-II (built of [→3)-α-D-Galp-(1→3)-β-D-Galp-(1→] repeating units). Galactan-I is present as the sole polymer in O2 serotype. Recently, in case of serotype O2, conversion of galactan-I to galactan-III (→3)-β-D-Galf-(1→3)-[α-D-Galp-(1→4)]-α-D-Galp-(1→) was reported. Substitution of →3)-α-D-Galp by a branching terminal α-D-Galp was dependent on the presence of the gmlABC operon and had a major impact on the antigenicity of the galactan polymer. Genetic analysis indicated that also 40% of the O1 clinical isolates carry the gmlABC locus; therefore we aimed to characterize the corresponding phenotype of LPS O-antigens. The presence of galactan-III among O1 strains was proven using galactan-III-specific monoclonal antibodies and confirmed by structural analyses performed using sugar and methylation analysis as well as classical and high-resolution magic angle spinning NMR spectroscopy. By using an isogenic mutant pair, we demonstrated that galactan-III expression was solely dependent on the presence of glycosyltransferases encoded by gmlABC, as was shown previously for the O2 serotype. Furthermore, the galactan-II structures in O1gml+ strains remained unaffected corroborating no functional interactions between the biosynthesis of galactan-III and galactan-II polymers.